Trust and Innovation Within the Firm: Evidence from Matched CEO-Firm Data - Nguyen, Kieu-Trang (Quarterly Journal of Economics, 2026)
This article shows that a CEO’s trust enhances innovation within a firm, providing a novel micro-foundation for the well-known trust-growth relationship. I build a new matched CEO-firm-patent data set covering 5,753 CEOs in 3,598 U.S. public firms and 700,000 patents during 2000–2011. I exploit variation in generalized trust across CEO ethnic origins, inferred from their last names using deanonymized historical censuses. Following CEO turnovers, a one standard deviation increase in a CEO’s generalized trust is associated with 6% more future patents and 4%–6% higher average patent quality, driven entirely by higher-quality patents. Text analysis of employee reviews shows that the CEO’s trust enhances a firm’s trust culture. These results are consistent with insights from qualitative interviews suggesting that the CEO's trust and the firm’s trust culture encourage researchers to undertake high-risk explorative research and development. In addition, changes in the CEO’s bilateral trust toward inventors in different countries have comparable effects on inventors’ patenting, controlling for CEO and other fixed effects.